Effect of Loyalty, Awareness, Social Media Platforms, and Social Influencers on the Growth of the Fashion Industry in Nepal - Maharjan, Selina; Tamrakar, Sujal; Gurung, Tenzing; Shrestha, Sushant (New Perspective: Journal of Business and Economics, 2024)
This research paper investigates the various factors contributing to the overall growth of the Nepalese fashion industry, focusing on the roles of customer loyalty, brand awareness, social media platforms, and social influencers. A quantitative analysis was conducted using data collected from 100 respondents residing in the Kathmandu Valley. The respondents, primarily fashion consumers and social media users, completed a set of questionnaires utilizing a 5-point Likert Scale. The data was analyzed using ANOVA, regression analysis, and correlation analysis to identify the specific factors driving the expansion of the fashion sector in Nepal. The findings reveal that brand awareness, the use of social media platforms, and the influence of social influencers significantly contribute to the growth of the Nepalese fashion industry. In contrast, customer loyalty was found to have no significant effect on this growth. Understanding these contributing factors allows brands and retailers to better comprehend consumer behavior and formulate effective strategies to enhance their market presence in the fashion industry. The study suggests that fashion brands should focus on increasing brand awareness and leveraging social media platforms and influencers to engage consumers effectively. Future research could explore the long-term effects of these factors on consumer behavior and industry growth.